2020
DOI: 10.1016/j.fuproc.2020.106548
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of aromatic selection towards newer formulated fuels for regulated and unregulated emissions reduction in CI engine

Abstract: The fuel composition highly affects formation of toxic pollutants in a diesel engine. The aromatics are found to be prominent fuel components that affect pollutant formation and at the same time help provide lubricity to moving engine parts. Therefore, their effect needs to be addressed systematically. This article elucidates aromatic types and its content effects on fuel atomization, regulated and unregulated emissions. Acoustic emission signals were also recorded for engine noise diagnosis during the exhaust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In research on bioadditives present in gasolines, it was found that MTBE and ETBE slightly increase NO x emissions [142], while the addition of bioethanol may lead to a decrease in NO x concentration [150]. The literature also indicates the formation of combustion byproducts [151] such as formaldehyde and acetaldehyde [142,152,153], acetone, propanal, benzaldehyde and tolualdehyde [154], and mono-and dicarboxylic acids [155,156].…”
Section: Physicochemical Composition Of Fuelmentioning
confidence: 99%
“…In research on bioadditives present in gasolines, it was found that MTBE and ETBE slightly increase NO x emissions [142], while the addition of bioethanol may lead to a decrease in NO x concentration [150]. The literature also indicates the formation of combustion byproducts [151] such as formaldehyde and acetaldehyde [142,152,153], acetone, propanal, benzaldehyde and tolualdehyde [154], and mono-and dicarboxylic acids [155,156].…”
Section: Physicochemical Composition Of Fuelmentioning
confidence: 99%
“…Although toluene and α-methylstyrene are benzene series, their performance is the worst in the benzene series, and their specific energy is also low. Methylnaphthalene fuelled combustion system emitted higher pollutants due to their higher degree of unsaturation and poor specific energy, and hence ranks last [50,51].…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…The ever-increasing demand for energy overburdens the existing resources of fossil fuels and results in escalating fuel prices . A looming energy crisis in front of us must be addressed with the utmost priority . More than 85% of the energy demand is fulfilled through the use of fossil fuels .…”
Section: Introductionmentioning
confidence: 99%
“…1 A looming energy crisis in front of us must be addressed with the utmost priority. 2 More than 85% of the energy demand is fulfilled through the use of fossil fuels. 3 Renewables such as biomass, solar, hydropower, and wind energy are considered as possible solutions to fulfill the current energy demand.…”
Section: Introductionmentioning
confidence: 99%